Pengaruh Kepercayaan Konsumen Terhadap Minat Beli Belanja Secara Online Pada Mahasiswa Universitas Negeri Padang - Alfionita Alfionita; Annur Fitri Hayati (Universitas Negeri Padang, 2023)
This study set out to determine how student interest in internet purchasing atPadang State University was impacted by consumer trust. A descriptive quantitativeresearchdesign was adopted for this investigation. The study’s sample was made up ofPadang State University students. The number of study samples, which may reach 97,was determined using the Cochran formula, and they were selected using a non-probability sampling approach and purposive sampling technique. Students at PadangState University were given questionnaires with pre-written questions in order to collectthe data. The analytical method employed is simple regression analysis with SPSS 20.The results show that Trust has a considerable impact on Purchase Intention.